S137 Vascular Endothelial Growth Factor (vegf) Expression In The Ipf Lung – A Role For Anti-angiogenic Isoforms?. (10th November 2014) - Barratt, SL; Blythe, T; Jarrett, C; Welsh, GI; Ourradi, K; Scotton, C; Bates, DO; Millar, AB
Abstract : Introduction: VEGF has been implicated in the pathogenesis of IPF. Differential splicing of the VEGF gene produces an alternative family of isoforms (VEGFxxx b) that have anti-angiogenic properties, in contrast to conventional isoforms (VEGFxxx ). Currently available literature on the role of VEGF in IPF has not differentiated between these families of isoforms and thus a degree of literature re-appraisal is required. Hypotheses The balance of VEGFxxx :VEGFxxx b isoforms may be important in IPF pathogenesis VEGFxxx b isoforms may abrogate the development of IPF Methods: Human lung sections and BALF were used to quantify isoform expression in the IPF lung and were compared to controls (ELISA and IHC). Explanted 'normal' (NF) and 'fibrotic' (FF) fibroblasts were grown in culture with subsequent total RNA and cell lysate extraction (qPCR and WB). Wild-type mice were administered bleomycin (BLM) then received bi-weekly therapeutic intraperitoneal (IP) injections of rhVEGF165 b (from day 10). Fibrosis was assessed histologically (Masson's Trichrome and Lung fibrosis score). Results: In the IPF lung, the alveolar epithelium was the most prominent site for total VEGF (PanVEGF isoforms) but also for VEGF165 b (n = 10). Addiitonal staining was noted in fibroblasts and lung inflammatory cells. Alveolar and fibrotic cells in the least fibrotic areas of the IPF lung expressed significantly less VEGF165 b than severely fibrotic areas (p < 0.001, n = 10). Examination of IPF BALF by ELISA revealed that total VEGF expression was significantly lower compared to control (IPF: 18.04 pg/ml +/- 6.13 n = 15, CTRL 85.72 pg/ml +/- 17.08 n = 13), whilst VEGF165 b could not be detected in identical samples. Explanted NF and FF express comparable quantities of VEGFxxx and VEGFxxx b isoforms at the mRNA and protein level. Rh VEGF165 increases the mRNA expression of fibronectin (p < 0.001, n = 4) an effect not seen following the administration of rhVEGF165 b. Administration of rhVEGF165 b to mice attenuated the development of BLM-induced pulmonary fibrosis (Masson's Trichrome (Figure 1 ) and lung fibrosis score (mean score: BLM alone 41.20 vs VEGF165 b 30.67, p < 0.01, n = 6 per group)). Conclusion: Differential expression of VEGFxxx and VEGFxxx b isoforms occurs in the IPF lung. In vitro, recombinant proteins appear to have differential effects on ECM synthesis and in vivo attenuate the formation of pulmonary fibrosis. A mouse overexpressing VEGF165 b in the lung has been developed to study this concept in greater detail.